Procedimentos comunicacionais necessários para uma relação eficiente entre o poder público e sociedade : a construção de um saber conjunto - Biffignandi, Fernando (2018)
This thesis deals with Public Communication, produced by government, and its relationship with society, represented by socially, culturally and economically disadvantaged communities. Starting from the constitutional right to the information the research sought to refer the theoretical presuppositions of the communication to the procedures adopted by the public organizations in their relation with the user as instrument of citizenship and social insertion. The methodology was based on bibliographic review, documentary analysis and interviews with those responsible for the development and application of public communication policies. From the collected material was evaluated its effectiveness and legitimacy before the new programs of total quality in the transmission of information as a fundamental presupposition of democracy. The approach focused on the process of transmitting public information aimed at the marginalized segment of society, highlighting the importance of understanding their particular language and expression in their daily lives. The results obtained presented important contributory elements for the formation of new practices of Public Communication, based on the excellence of the relation that involves the State and the citizen. The information provided the recognition that each of these actions refers to the urgency of the participation of governments in social construction and the promotion of adequate policies for the benefit of the Brazilian population. The challenge of researching and proposing a communication methodology with the objective of guiding, integrating and passing on information at all levels, considering that participation through dialogue, as an effective methodological communication tool.